Intestinal stem cells. - Leedham, S; Brittan, M; McDonald, SA; Wright, N (2005)
The intestinal tract has a rapid epithelial cell turnover, which continues throughout life. The process is regulated and maintained by a population of stem cells, which give rise to all the intestinal epithelial cell lineages. Studies in both the mouse and the human show that these cells are capable of forming clonal crypt populations. Stem cells remain hard to identify, however it is thought that they reside in a 'niche' towards the base of the crypt and their activity is regulated by the paracrine secretion of growth factors and cytokines from surrounding mesenchymal cells. Stem cell division is usually asymmetric with the formation of an identical daughter stem cell and committed progenitor cells. Progenitor cells retain the ability to divide until they terminally differentiate. Occasional symmetric division produces either 2 daughter cells with stem cell loss, or 2 stem cells and eventual clone dominance. This stochastic extinction of stem cell lines with eventual dominance of one cell line is called 'niche succession'. The discovery of plasticity, the ability of stem cells to engraft into, and in some cases replace the function of damaged host tissues has generated a large amount of scientific and clinical interest: however the concept remains controversial and is still a subject of hot debate. Studies are beginning to identify the complex molecular, genetic and cellular pathways underlying stem cell function such as Wnt signalling, bone morphogenetic protein (BMP) and Notch/Delta pathways. The derangement of these pathways within stem cells plays an integral part in the development of malignancy within the intestinal tract.